Interactive Excel E-Module for Grade VII Informatics Learning - Sofyan, M.; Haris , Celine Aloyshima (Universitas Muhammadiyah Sidoarjo, 2025)
This research aims to develop e-modules for seventh grade Informatics subject on Excel introduction material and evaluate teacher and learner responses using the 4D development model. The defining stage includes initial analysis, learner analysis, and preparation of learning objectives, which show the need for e-modules because there are no special modules available and only rely on online materials. The e-module design is organized according to the learning outcomes of Merdeka Curriculum and packaged in an attractive format using Word, Canva, and Flip PDF Corporate, complete with text, videos, and quizzes. Validation by three media experts and one material expert resulted in an average score of 80.58% (“Valid”), so the product was fully developed and published electronically. Responses to the e-module were collected from one teacher and 74 students, with results of 92.5% for teachers and 83% for learners-both rated “Excellent”. The e-module was further disseminated through links and QR codes. Although the technical use of the free Flip PDF to bring up watermarks and coordination during response collection was difficult, this product proved to be effective, innovative, and feasible to use in informatics learning. Highlights: Needs-Based Design – Developed due to lack of specific Excel modules. Validated & Rated Excellent – Expert and user evaluations showed high effectiveness. Multimedia Integration – Included videos, quizzes, and engaging formats for better learning. Keywords: E-Module Development, Informatics Learning, Merdeka Curriculum, Flip PDF, Student Engagement